Psychological risk profile for overuse injuries in sport: An exploratory study - Martin, S.; Johnson, U.; McCall, A.; Ivarsson, A. (Journal of Sports Sciences, 2021)
Overuse injuries account for a substantial part of sport injury incidence among athletes of various sports and levels. Despite the gradual onset of symptoms, athletes often persevere in training and competing. The present exploratory study aimed to identify a psychological risk profile for overuse injury. One hundred and forty-nine athletes competing in various sports responded to a range of questionnaires measuring the following psychological variables: negative life stress, perfectionistic concerns, perfectionistic strivings, athletic identity, and the coach-athlete relationship. Participants subsequently answered the OSTRC Overuse Injury Questionnaire on a weekly basis during a 10-week period. Using a latent profile analysis, athletes were classified into three latent profiles regarding their psychological characteristics. Athletes in the second profile, characterized by a combination of high athletic identity, perfectionistic concerns and negative life stress and poor coach-athlete relationship, were found to be significantly more often affected by overuse injuries (74% of the time) than individuals in the two other profiles (52% and 48% of the time, respectively). In conclusion, psychological factors may contribute to the risk of overuse injuries through complex interactions (i.e. accounting for interdependencies within a specific configuration of variables) rather than through their independent influences.